Medak District Plan 1980-85 Draft Government of Andhra Pradesh - Planning Commission (Planning Commission, 1980)
Medak district extends over an area of 9,685 Sq. Kms. accounting for 3.5 per cent of the total area of the State. The total population of the District in 1971 was 14.68 lakhs accounting for 3.4 per cent of the State’s total population. The District is bounded by Nizamabad and Karimnagar districts on the North, Ranga Reddy district on the South, Warangal and Nalgonda districts on the East and Bidar district of the Karnataka State on the West.
Finance and Planning Department, Government of Andhra Pradesh